The institutional framework model for the implementation of the EU cohesion policy in Croatia for the 2021-2027 programming period - Zvonimir Savić (Ekonomski Vjesnik, 2020)
The EU cohesion policy is considered one of the most important policies implemented and financed through the EU common budget, as about a third of the EU budget is allocated to funds that are instruments of that policy. The goal of the EU regional policy is to reduce development disparities between EU regions by co-financing development projects. Given that the less developed regions benefit the most from this policy, it is extremely important for Croatia because it directly affects the country’s economic and social development and helps it converge towards the EU average. Considering the above, this paper seeks to contribute to the scientific discourse on the use of regional policy funds by examining the topic beyond temporal boundaries of programming periods and by proposing an institutional framework model for the management of the EU regional policy instruments in Croatia. To empirically determine the key institutional factors in the absorption of EU funds, the paper considers the existing EU fund management systems of selected EU countries. Through scientific research and comparative analysis of management systems in nine Central and Eastern European countries and drawing on the experience of the Croatian system and its functioning, an optimal model for the management of the EU regional policy funds at the national level was formulated. The proposed model should improve strategic decision making by the executive branch and help Croatia make the best possible use of EU regional policy funding, which should in turn reflect positively on economic growth.